NEW GEOCHEMICAL INSIGHTS INTO CENOZOIC SOURCE ROCKS IN AZERBAIJAN: IMPLICATIONS FOR PETROLEUM SYSTEMS IN THE SOUTH CASPIAN REGION. (26th June 2021) - Aghayeva, V.; Sachsenhofer, R. F.; van Baak, C.G.C.; Bechtel, A.; Hoyle, T. M.; Selby, D.; Shiyanova, N.; Vincent, S. J.
Abstract : The Maikop Group and the Diatom Formation constitute the two main source rocks in the South Caspian Basin and onshore Azerbaijan where large‐scale oil production began more than 150 years ago. However, the stratigraphic distribution of the source rocks and the vertical variation of source‐rock parameters are still poorly understood. The aim of the present paper is therefore to investigate in high resolution the source‐rock distribution in the Perekishkyul and Islamdag outcrop sections, located 25 km NW of Baku, which provide nearly complete middle Eocene and lower Oligocene to upper Miocene successions. Bulk geochemical parameters of 376 samples together with maceral, biomarker and isotope data were analysed. In addition, new Re/Os data provide independent age dating for the base of the Upper Maikop Formation (30.0 ± 1.0 Ma) and the paper shale within the Diatom Formation (7.2 ± 2.6 Ma). The presence of steradienes in high concentrations demonstrates the thermal immaturity of the studied successions, limiting the application of some biomarker ratios. Intervals with high TOC contents and containing kerogen Type II occur near the top of the middle Eocene succession. However, because of the low net thickness, these sediments are not considered to constitute significant hydrocarbon (HC) source rocks. The Maikop Group in the Islamdag section is 364 m thick and represents lower Oligocene (upper Solenovian) to middle Miocene (Kozakhurian) levels. Samples are characterized by moderately high TOC contents (∼1.8 wt.%) but low hydrogen index (HI) values (average ∼120 mgHC/gTOC) despite a dominance of aquatic organic matter (diatoms, methanotrophic archaea and sulphate‐reducing bacteria). Rhenium‐osmium chronology suggests low sedimentation rates (∼25 m/Ma), which may have had a negative impact on organic matter preservation. Terrigenous organic matter occurs in variable but typically low amounts. If mature, the Maikop Group sediments at Islamdag could generate about 2.5 tHC/m 2 . The Diatom Formation includes a 60 m thick paper shale interval with high TOC contents (average 4.35 wt.%) of kerogen Type II‐I (HI up to 770 mgHC/gTOC). The source potential is higher (∼3 tHC/m 2 ) than that of the Maikop Group. The organic matter is dominated by algal material including diatoms. High TOC/S ratios suggest deposition under reduced salinity conditions. Strictly anoxic conditions are indicated by the presence of biomarkers for archaea involved in methane cycling. For oil‐source correlations and a better understanding of the petroleum system, it will be necessary to distinguish oil generated by the Maikop Group from that generated by the Diatom Formation. This study shows that these oils can be distinguished based on the distribution of specific biomarkers e.g. C30 steranes, C25 highly branched isoprenoids (HBIs), and the C25 isoprenoid pentamethylicosane (PMI).